Smart card-based secure authentication protocol in multi-server IoT environment - Bae, Won il; Kwak, Jin (Multimedia Tools and Applications, 2020)
In recent years, the internet of things has been widely utilized in various fields, such as in smart factories or connected cars. As its domain of application has expanded, it has begun to be employed using multi-server architectures for a more efficient use of resources. However, because users wishing to receive IoT(Internet of Things) services connect to multi-servers over wireless networks, this can expose systems to various attacks and result in serious security risks. To protect systems (and users) from potential security vulnerabilities, a secure authentication technology is necessary. In this paper, we propose a smart card-based authentication protocol, which performs the authentication for each entity by allowing users to go through the authentication process using a smart card transmitted from an authentication server, and to login to a server connected to the IoT. Furthermore, the security of our proposed authentication protocol is verified by simulating a formal verification scenario using AVISPA(Automated Validation of Internet Security Protocols and Applications), a security protocol-verification tool.
Keywords: Authentication protocols; Multi-server; Multi-server architecture; Secure authentications; Security; Security protocol verification; Security vulnerabilities; User authentication; Formal verification; Internet of things; Multi server; Security; User authentication